Evaluation of arc quenching ability for SF6 replacements based on time-dependent Elenbaas–Heller and Boltzmann equations - Ren, He; Zhong, Linlin (Journal of applied physics, 2025)
Sulfur hexafluoride (SF6), a widely used arc quenching medium in the power industry, has been designated as a greenhouse gas, necessitating its reduction and replacement. Identifying eco-friendly alternatives to SF6 is a complex and expensive process, particularly since these alternatives often consist of gas mixtures that may function at varying pressures. In this work, we propose an efficient method for evaluating the arc quenching performance of gases or gas mixtures using the time-dependent Elenbaas–Heller and Boltzmann equations, which circumvents the computational costs associated with traditional 2D or 3D magnetohydrodynamic arc models. We segment the arc quenching process into four distinct stages: the thermal recovery stage, pre-dielectric recovery stage, post-dielectric recovery stage, and residual-gas cooling stage. To quantitatively assess arc quenching performance, we introduce two key parameters: recovery rate and recovery strength. The recovery rate is defined as the harmonic mean of thermal, pre-dielectric, and post-dielectric recovery rates. The recovery strength is characterized by the harmonic mean of the average recovery voltage, maximum critical electric field strength, and room-temperature dielectric strength. Our method is validated using several SF6 alternatives, including SF6 mixtures, C4F8, C4F7N, C5F10O, and their mixtures with CO2, N2, and O2. The results demonstrate that the coupling of the time-dependent Elenbaas–Heller and Boltzmann equations well describes the arc decaying process. Moreover, the proposed recovery rate and recovery strength metrics effectively quantify the arc quenching ability, enabling a systematic and efficient evaluation of various gas mixtures for arc interruption performance.